2008
DOI: 10.1073/pnas.0804054105
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β in proliferative vitreoretinal diseases and ROCK as a therapeutic target

Abstract: Cicatricial contraction of preretinal fibrous membrane is a cause of severe vision loss in proliferative vitreoretinal diseases such as proliferative diabetic retinopathy (PDR) and proliferative vitreoretinopathy (PVR). TGF-␤ is overexpressed in the vitreous of patients with proliferative vitreoretinal diseases and is also detectable in the contractile membranes. Therefore, TGF-␤ is presumed to contribute to the cicatricial contraction of the membranes, however, the underlying mechanisms and TGF-␤'s importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 37 publications
7
124
0
5
Order By: Relevance
“…Our recent experiments have confirmed that repeated intravitreal injections of fasudil at a final concentration of 30 mol/l in rabbit eyes and single intravitreal injection of fasudil up to 100 mol/l in rat eyes did not cause apparent electrophysiological or morphological changes in retinal tissues or induction of inflammatory cells, compared with the untreated control eyes (36). Intravitreal injection of vehicle also did not cause significant leukocyte adhesion or endothelial damage in rat retinas, compared with untreated control.…”
Section: Discussionsupporting
confidence: 61%
“…Our recent experiments have confirmed that repeated intravitreal injections of fasudil at a final concentration of 30 mol/l in rabbit eyes and single intravitreal injection of fasudil up to 100 mol/l in rat eyes did not cause apparent electrophysiological or morphological changes in retinal tissues or induction of inflammatory cells, compared with the untreated control eyes (36). Intravitreal injection of vehicle also did not cause significant leukocyte adhesion or endothelial damage in rat retinas, compared with untreated control.…”
Section: Discussionsupporting
confidence: 61%
“…of TGF-β signaling (26,27). Strikingly, p-MLC was significantly decreased (despite increased MLC expression) early after TβRII knockdown, and it persisted long-term ( Figure 4, C and D, and Supplemental Figure 9B).…”
Section: Figurementioning
confidence: 85%
“…[8][9][10] Furthermore, TGF-b mediates contraction of preretinal membranes. 11 TGF-b is induced in the vitreous in proliferative diabetic retinopathy and proliferative vitreoretinopathy. [12][13][14] Matrix metalloproteinases (MMPs) are calcium-or zinc-dependent extracellular proteolytic enzymes that have a role in degrading and remodelling of extracellular matrix in various physiological and pathological conditions including ischemic vitreoretinal eye diseases.…”
Section: Introductionmentioning
confidence: 99%